A trajetória de José Oiticica: o professor, o autor, o jornalista e o militante anarquista na educação brasileira - Figueira, Cristina Aparecida Reis (2008)
This is a study of the trajectory and formation path of the cathedratic from Colégio Pedro II and anarchist militant José Rodrigues de Leite e Oiticica (1882-1957), educator involved in actions of social libertarian propaganda in newspapers, in free thought conferences, in the social theater as well as in educational projects that circulated in differentiated patterns in the history of Brazilian education. Author of useful intellectual production related to the studies of linguistics, literature, music, poetry, theater and also the anarchist ideology, whose expressiveness can be found in numerous articles for the anarchist press as well as for the great carioca press, in his didactic manuals, his plays, his sonnets and in his sociological essays. The research gathered elements José de Oiticica the intellectual production and his life path and had as objective to map his critics and prescriptions of the practices of the social propaganda for the rebuilding of his project for the libertarian education, of the social propaganda and his performance as a Portuguese teacher at the Colégio Pedro II, through the exam of his journalistic articles, books, booklets as well as classes manuscripts, active and passive correspondence and incursions in the historiographies of the working class and Brazilian education, in educational projects that circulated in different models above all in the period between the years 1905 and 1950. In the construction of the research was sought his sociability nets and relationships, a procedure that evidences one of the main purpose of the research, which is the one that subjects are constituted in the extent of the social practices, considering the relationships that they are involved in, of the actions that they promote which are inherited, all of them dynamics and contradictory. Starting from the interrogated evidence treated by E. P Thompson, we tried to build the research in observation the appropriate logic to the materials gathered in the research, in observation of the content sequence detected by the exam of primary sources, through the reconstitution of documents and the dialogue with the sources following their indication, tracks and signs under the inspiration of Carlo Ginzburg. Besides the treatment with the primary sources, the research accomplished oral interviews and also worked with his former student s texts and also with the militant s memory preserved in the historiography of the Brazilian working class. The rebuilding of the José Oiticica educational project is justified for the fact of bringing for the debate some of the principles that guided the experiences of the lived in the projects of the libertarian education, that in the wrong way of the reactionary pessimism and the naïve optimism, had the beginning of reflection, of the actions addressed to individual education projects, of small groups and maybe collective, and mainly for the fact of the research to be a contribution to the educational debate on the patterns of education considered won, particularly the related to projects of the anarchist education